The extraterritorial human rights obligations of Japan in regard to Fukushima nuclear contaminated water - Yu, Liang; Xu, Weizhuo (Frontiers in Marine Science, 2023)
This article adopts a human rights approach to observe Japan's policy on releasing nuclear contaminated water into the Pacific Ocean. It aims to provide a new discourse for stakeholders to push Japan to deal with Fukushima's water in a responsible way. In doing so, it needs to elucidate an important normative question, namely whether a State has extraterritorial human rights obligations, given that international human rights law was traditionally perceived to deal with relationship between a State and its population. This stereotype would frustrate the world people to challenge the Japan's decision based on human rights. In the era of economic globalization, however, there is an increasing need for the extraterritorial application of human rights treaties. Human rights theory and practice have gradually developed the jurisprudence on extraterritorial obligations of States based on an interpretation of jurisdiction. Such an approach has expanded from regulating State overseas military actions to tackling trans-boundary environmental harms. In the latter sense, the Fukushima incident is a good case, which urgently calls for a comprehensive examination of Japan's extraterritorial human rights obligations. This article undertakes such a task by providing a logical interpretation of human rights treaty provisions. It is argued that the release of nuclear contaminated water entails a variety of extraterritorial obligations to respect, protect, and fulfill human rights on the part of Japan.